Impacto da pandemia de Covid-19 no autorrelato de bruxismo do sono em adolescentes de Santa Maria-RS - Lito, Marcia Farias Pereira (2022)
The COVID-19 pandemic brought many changes in routine and in life and health habits, especially for children and adolescents. The implementation of social distancing caused changes in lifestyle, causing, in many people, psychological, financial, emotional, behavioral and sleep changes, such as bruxism. These aspects can harm the quality of life of individuals. The objective of this research is to evaluate the impact of the COVID-19 pandemic on the occurrence of sleep bruxism (SB) in adolescents, over a year and three months after the onset of the COVID-19 pandemic. A total of 290 adolescents between 11-15 years old who study in public and private schools in the city of Santa Maria - RS, Brazil participated in this research. Data were collected at 3 different moments: before the beginning of the pandemic in person (T1), 3 months (T2) and 1 year and 3 months (T3) after the beginning of the COVID-19 pandemic through telephone contact. Parents/legal guardians and adolescents answered questionnaires about socioeconomic and psychosocial aspects. The Self-Reported Bruxism Question: “Do you grind your teeth in your sleep?” was answered by the teenagers. For statistical analysis, the program STATA 14.0 (Stata Corporation, College Station, TX, USA) was used. Multilevel, adjusted, logistic regression models, for repeated measures, with random effect were used to evaluate the changes in the occurrence of SB during T1, T2 and T3. In the descriptive analysis, there was an increase in the occurrence of self-reported bruxism among adolescents from 13%, before the COVID-19 pandemic, to 22% after 1 year and 3 months of its onset. The adjusted Poison Logistic Regression analysis showed no difference in the chance of having SB at T2 when compared to T1 (OR 0.70 95%CI 0.37–1.35). However, in the long term, the frequency of SB increased significantly at T3, with a 2.6 times greater chance of having SB when compared to T1 (OR 2.60 95%CI 1.49–4.54). Thus, this study observed a considerable increase in the self-report of SB in adolescents and understands that this increase may be associated with the socioeconomic and psychosocial changes caused by the COVID-19 pandemic.